Expectations vs customer satisfaction: the case of luxury hotels - Santos, Sílvia (2020)
Customer expectations and satisfaction has been one of the most studied themes in marketing literature among several business areas. In the hospitality sector, these themes are crucial regarding the specific characteristics of the service but also the huge competitiveness in this field. Nowadays, in hospitality, it is current practice to evaluate customer satisfaction, but few studies relate this satisfaction with their expectations. This study aims to characterize the customer expectations with the services provided by luxury hotels and to characterize the luxury market in hospitality. To answer our objectives a quantitative study was conducted. Participated in our study 330 hotel customers, of both genders, with a mean age of 46,8 years (SD=13,9), from five luxury hotels. All the participants fulfilled a questionnaire with sociodemographic questions and several questions assessing the satisfaction level with the different services provided by the hotels. Statistical analysis, descriptive and inferential, were performed with SPSS 24.0. The preliminary results showed that luxury hotels customers made a positive or very positive evaluation of the services provided by the different hotels of the group. The relation between the same kind of service performed is significant, ie, when the customer considers the quality of the bar important also asses as important the quality and diversity of the restaurant. In the same way, the group seems to have some differences among the services provided by specific kinds of hotels. Thus, we can conclude that customers' satisfaction is very important to the services provided by hotels, namely in the luxury market. Moreover, the luxury market seems to be a tendency in the hospitality sector. We discuss the main practical and theoretical implications and offer some suggestions for further studies.